Vancomycin sorption on activated sludge Gram+ bacteria rather than on EPS; 3D Confocal Laser Scanning Microscopy time-lapse imaging. (1st November 2017) - Louvet, J.N.; Carrion, C.; Stalder, T.; Alrhmoun, M.; Casellas, M.; Potier, O.; Pons, M.N.; Dagot, C.
Abstract: Antibiotics-bacteria interactions depend on antibiotic concentration at the scale of bacteria. This study investigates how vancomycin penetrates into activated sludge flocs and can be sorbed on the bacteria and extracellular polymeric substances (EPS). The 3D structure of flocs was imaged using EPS autofluorescence. The green fluorescent BODIPY ® FL vancomycin was introduced in a microscopic chamber containing activated sludge and penetration of vancomycin into the flocs by diffusion was observed using time-lapse microscopy. The penetration depended on the floc structure, as long and large pores could go through the whole flocs making preferential path. The antibiotic concentration into the flocs was also found to depend on the sorption rate. BODIPY ® FL vancomycin was found to bind preferentially into Gram + bacteria than on EPS. The vancomycin adsorption constant on bacteria according to the linear adsorption model, Kdbacteria was estimated to be 5 times higher (SD 2.6) than the adsorption constant on EPS KdEPS . These results suggest that antibiotic removal by sorption into wastewater treatment plants could change according to the amount of bacteria in the sludge. Moreover, antibiotic concentration at the scale of bacteria could be significantly higher than the concentration in the bulk solution and this should be taken into account when studying antibiotic activity or biodegradation. Graphical abstract: Highlights: Vancomycin concentration in the flocs was found to depend on the local sorption rate. Vancomycin was found to bind preferentially to Gram + bacteria than on EPS. Vancomycin concentration in bacteria was 5 times higher than in EPS. The 3D structure of flocs was imaged using the EPS blue auto-fluorescence.